Auxetic nuclei in embryonic stem cells exiting pluripotency - Pagliara, Stefano; Franze, Kristian; Mcclain, Crystal R.; Wylde, Georgew.; Fisher, Cynthia L.; Franklin, Robin J. M.; Kabla, Alexandre J.; Keyser, Ulrich F.; Chalut, Kevin J. (Nature Materials, 2014)
Embryonic stem cells (ESCs) self-renew in a state of naïve pluripotency in which they are competent to generate all somatic cells. It has been hypothesized that, before irreversibly committing, ESCs pass through at least one metastable transition state. This transition would represent a gateway for differentiation and reprogramming of somatic cells. Here, we show that during the transition, the nuclei of ESCs are auxetic: they exhibit a cross-sectional expansion when stretched and a cross-sectional contraction when compressed, and their stiffness increases under compression. We also show that the auxetic phenotype of transition ESC nuclei is driven at least in part by global chromatin decondensation. Through the regulation of molecular turnover in the differentiating nucleus by external forces, auxeticity could be a key element in mechanotransduction. Our findings highlight the importance of nuclear structure in the regulation of differentiation and reprogramming. © 2014 Macmillan Publishers Limited.
CRIS-Team Scopus Importer:2020-08-12